Potential for flexible lactate shuttling between astrocytes and neurons to mitigate against diving-induced hypoxia - Ciccone, Chiara; Dötterer, Sari Elena; Vold Jensen, Sigrid; Geßner, Cornelia; West, Alexander C.; Wood, Shona H.; Hazlerigg, David G.; Folkow, Lars P. (Frontiers in Neuroanatomy, 2025)
For most non-diving mammals, lack of O2 (hypoxia) has detrimental effects on brain function. Seals, however, display a series of systemic, cellular, and molecular adaptations that enable them to tolerate repeated episodes of severe hypoxia. One as yet unresolved question is whether seal neurons in part employ anaerobic metabolism during diving: the “reverse astrocyte-neuron lactate shuttle” (rANLS) hypothesis postulates that seal neurons, by shuttling lactate to the astrocytes, may be relieved (1) from the lactate burden and (2) from subsequent ROS-production as lactate is oxidized by astrocytes upon re-oxygenation after the dive. Here, we have investigated this possibility, through histological and functional comparisons of the metabolic characteristics of neocortical neurons and astrocytes from the deep-diving hooded seal (Cystophora cristata), using mice (Mus musculus) as a non-diving control. We found that seal astrocytes have higher mitochondrial density and larger mitochondria than seal neurons, and that seal neurons have an atypical and significantly higher representation of the monocarboxylate lactate exporter MCT4 compared to mouse neurons. Also, measurements of mitochondrial O2 consumption suggest that the aerobic capacity of primary seal astrocytes is at least equal to that of primary seal neurons. Transcriptomics data from seals vs. mice suggest that specific adaptations to the electron transport system in seals may contribute to enhance hypoxia tolerance. These observations are consistent with the rANLS hypothesis.